Role of Interventional Radiology in the Management of Vascular Lesions around the Knee Joint: A Series of Four Cases - Vishal Nandkishor Bakare; Pratiksha Yadav; Ravi Arya; Ritesh Sahu (Journal of Clinical and Diagnostic Research, 2023)
The soft tissue lesions around the knee range from congenital, traumatic, and vascular to neoplastic in aetiology. The various imaging modalities employed for diagnostic work-up include plain radiographs, ultrasonography, Computed Tomography (CT) scan, and Magnetic Resonance Imaging (MRI). Based on the peculiar imaging findings, the differential diagnosis can be narrowed down; however, the final diagnosis relies on histopathological findings. Some of the highly vascular lesions are arteriovenous malformation, malignant fibrous histiocytoma, haemangiopericytoma, and synovial sarcoma. The abundant neovascularity within these lesions poses a major problem during surgery due to potential blood loss. Presurgical interventional management in the form of endovascular embolisation significantly reduces intraoperative blood loss. Here, four different cases, one of each type, presenting as highly vascular lesions around the knee joint, were successfully managed with endovascular embolisation.